Usability testing essentials : ready, set-- test! - Barnum, Carol M. (Morgan Kaufmann Publishers, 2011)
Do you love your mobile phone? Your MP3 player? Your e-book reader? You laptop or tablet PC? There's a reason for that. Usability. When usability testing is part of the design and development of products, the results are better products that users want and like. You may be doing testing now or want to help your company get started, but you may not have all the tools to know how to properly prepare, test, analyze, and measure the results across a multitude of cultures, generations, and countries. And you may be facing tight budgets and short timeframes for testing. If this is your situatio.